2010
DOI: 10.14714/cp65.128
|View full text |Cite
|
Sign up to set email alerts
|

Non-Connective Linear Cartograms for Mapping Traffic Conditions

Abstract: Cartograms have the advantage of bringing a greater visual impact to map readers. Geographic locations or spatial relationships of objects are intentionally modified to suit the attributes pertaining to objects. In area cartograms, it is the size of the object that is intentionally modified, while in linear cartograms it is the length or direction that is intentionally modified. Traffic conditions in urban transportation networks are very dynamic phenomenon as they change through time. During highly congested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Shimizu and Inoue [17] reported that cartograms are a highly effective method for visually representing statistical data. Similarly, Wu and Hung [18] found cartograms very useful for creating strong visual impacts.…”
Section: Introductionmentioning
confidence: 91%
“…Shimizu and Inoue [17] reported that cartograms are a highly effective method for visually representing statistical data. Similarly, Wu and Hung [18] found cartograms very useful for creating strong visual impacts.…”
Section: Introductionmentioning
confidence: 91%
“…Since each link has a different performance, the vehicle group was classified by setting different thresholds for each link. Therefore, the Jenks natural break (JNB) was used as a technique for the clustering of traffic features and for searching for stateidentifying thresholds for a single property of urban traffic flows (37,38). The JNB method searches for thresholds that minimize the variance in the classification group and increase the variance among the classification groups.…”
Section: Vehicle Group Separationmentioning
confidence: 99%
“…Some researchers consider cartograms as a highly effective tool (e.g. Bhatt, 2006;Dent, 1975;Dorling, 1996;Inoue & Shimizu, 2006;Kocmoud & House, 1998;Shimizu & Inoue, 2009;Wu & Hung, 2012), while others have doubts about their effectiveness because of the possible deformation in shape (e.g. Fotheringham, Brunsdon, & Charlton, 2000;Griffin, 1980;Griffin, 1983;Roth, Woodruff, & Johnson, 2010;Tobler, 2004;Yau, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, cartograms have become an increasingly popular tool due to their captivating design (Bhatt, 2006;Kocmoud, 1997;Shimizu & Inoue, 2009), and also due to the availability of tools to create them automatically. A cartogram emphasizes attributes over geographic locations or spatial relationships, thereby attracting greater attention from readers and creating a strong visual impact (Wu & Hung, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation